DETERMINING THE LEVEL OF AWARENESS OF THE JUDICIAL SYSTEM OF UKRAINE - SKUTELNYK, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The issue of judicial system reform is extremely urgent for Ukrainian society, caused by the problem of trust in the judiciary. Taking into account the European vector of Ukraine's development, the reform of the judicial system of Ukraine is carried out by actively borrowing foreign experience and involving foreign experts in the process of preparing changes to the judicial legislation. The judicial system is one of the branches of state power, which is independent in its activities from other branches of government. It has exclusive powers of interpretation and is governed exclusively by the Constitution and laws of the state and is considered the sole dispenser of justice. The judicial system protects the interests of people and citizens from possible encroachments by the state and other subjects of public life. It covers all areas of relationships.The article examines the model of the level of reform of the judicial system in Ukraine, which covers the principles, functions, structure, and basic provisions on which the relations of the judiciary with the President, the Cabinet of Ministers, and the Verkhovna Rada are based. The package of amendments to the Constitution of Ukraine and laws related to the renewal of the judicial system was analyzed. Effective reform of the judicial system is aimed at ensuring that every citizen can exercise his right to access to justice without unjustified obstacles, so that society is confident in the independence and impartiality of the court when considering any legal conflict, regardless of the status of its participants, and the legal status of judges , bearers of judicial power, corresponded to the extremely important social and legal mission performed by the court.The article is devoted to the analysis of the production line of ship reform in Ukraine with an emphasis on the identification of these ongoing problems. The aim is to assess the effectiveness of the reforms and identify those aspects that require further attention and correction to achieve real changes in the judicial system of the country.
Keywords: judicial system; judicial power; justice; judiciary; reforming the judicial system